The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/la036093q
|View full text |Cite
|
Sign up to set email alerts
|

From Rolling Ball to Complete Wetting:  The Dynamic Tuning of Liquids on Nanostructured Surfaces

Abstract: In this work, for the first time, a dynamic electrical control of the wetting behavior of liquids on nanostructured surfaces, which spans the entire possible range from the superhydrophobic behavior to nearly complete wetting, has been demonstrated. Moreover, this kind of dynamic control was obtained at voltages as low as 22 V. We have demonstrated that the liquid droplet on a nanostructured surface exhibits sharp transitions between three possible wetting states as a function of applied voltage and liquid sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
426
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(447 citation statements)
references
References 31 publications
14
426
2
Order By: Relevance
“…From the above description of super-hydrophobicity and electrowetting, it appears that these two mechanisms are complementary with one providing an increase in hydrophobicity and the other a reduction simultaneously applicable to a single surface. In a recent report of electrowetting on nanostructured surfaces [6] it was demonstrated that dynamic electrical control of the wetting behavior of liquids could be achieved from superhydrophobicity to almost complete wetting. In this work we report studies of electrowetting on superhydrophobic surfaces of micro-patterned SU-8 photoresist structures.…”
Section: Introductionmentioning
confidence: 99%
“…From the above description of super-hydrophobicity and electrowetting, it appears that these two mechanisms are complementary with one providing an increase in hydrophobicity and the other a reduction simultaneously applicable to a single surface. In a recent report of electrowetting on nanostructured surfaces [6] it was demonstrated that dynamic electrical control of the wetting behavior of liquids could be achieved from superhydrophobicity to almost complete wetting. In this work we report studies of electrowetting on superhydrophobic surfaces of micro-patterned SU-8 photoresist structures.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from technological applications, EW has also proven to be a very useful tool for studying fundamental problems in wetting and thin film hydrodynamics, where the contact angle is often a crucial parameter that is difficult if not impossible to vary experimentally without changing other important aspects of the system. Examples include wetting of complex surfaces [3,4], capillary pinch-off and microdroplet generation [5][6][7], and deposition [8]. Frequently, electrowetting experiments are performed in an ambient oil bath in order to minimize both the evaporation of liquid and contact angle hysteresis.…”
mentioning
confidence: 99%
“…Another important phenomenon is also reported, i.e., the apparent contact angle will reduce suddenly at a critical voltage, because the liquid penetrates into the grooves [25,28]. The rate of change of the cosine of the contact angle is different before or after this critical voltage.…”
Section: Extended Electrowetting Equationmentioning
confidence: 89%
“…In an electrowetting experiment, one can achieve from superhydrophobicity to almost complete wetting for liquids on microstructured surfaces [28]. Another important phenomenon is also reported, i.e., the apparent contact angle will reduce suddenly at a critical voltage, because the liquid penetrates into the grooves [25,28].…”
Section: Extended Electrowetting Equationmentioning
confidence: 90%